Sultan of Pahang conferred Honorary Doctorate in Civil Engineering - UMP, PNC
His Royal Highness (HRH), the Sultan of Pahang, Sultan Ahmad Shah Al-Musta’in Billah Ibni Al-Marhum Sultan Abu Bakar Ri’ayatuddin Al-Mu’adzam Shah, was conferred an Honorary Doctor of Philosophy Degree in Civil Engineering by Universiti Malaysia Pahang (UMP) at the university’s Commemorative and 4th Convocation ceremonies held at UMP’s Sports Complex on October 3 last year.